El viejo Macdonald tenía una granja - Mlawer, Teresa; Adams, Pam (Bridgemead, Swindon, UK : Child's Play, 2016)
Una edicion de lengua espanola del libro popular Viejos Macdonald tenia una Granja. Ilustraciones animadas, innovador mueren cortando y rimas populares hacen Libros con Agujeros un debe para cada nino. Disponible en varios formatos, convenientes para bebes, ninos, pre-schoolers y el cuarto de ninos o aula.
A Spanish language edition of the popular book "Old Macdonald had a Farm". Bouncy illustrations, innovative die cutting and popular rhymes make Books with Holes a must for every child. Available in various formats, suitable for babies, toddlers, pre-schoolers and the nursery or classroom.
Keywords: Farms -- Juvenile literature; Folk songs, English -- United States -- Texts -- Juvenile literature; Domestic animals -- Juvenile literature; Folk songs, English -- Juvenile literature; Spanish language materials -- Juvenile literature; Animales domesticos -- Literatura juvenil; Granjas -- Literatura juvenil; Canciones folkloricas en ingles -- Estados Unidos -- Textos